Iridium(III) Complexes of Terpyridine‐ and Terpyridine‐Analogous Ligands Bearing Sugar Residues and Their in vitro Activity. Issue 21 (22nd June 2016) - Prokop, Aram; Czaplewska, Justyna A.; Clausen, Mara; König, Marcel; Wild, Andreas; Thorwirth, Rico; Schulze, Benjamin; Babiuch, Krzysztof; Pretzel, David; Schubert, Ulrich S.; Gottschaldt, Michael
Abstract : A series of terpyridine‐ and terpyridine‐analogous ligands bearing sugar moieties (glucose, galactose) attached through different glycosidic bonds ( S ‐glycosides, O ‐glycosides) and their iridium(III) complexes was synthesized and characterized. Their in vitro cytotoxicity was investigated, and one iridium complex with significant activity could be identified and studied in more detail. Dose‐dependent inhibition of cell growth was achieved at low concentrations (5 µm ). For reduction of proliferation by 50 % (ID50 ) the necessary concentration was 0.5 µm . The induction of apoptosis could be verified by flow‐cytometric determination of DNA fragmentation in BJAB cells after 72 h. Apoptosis induction of the iridium complex in drug‐resistant cells was tested with modified BJAB and Nalm‐6 cells and their nonresistant strains. The complex was able to induce apoptosis in 50 % of cells (AC50 ) in concentrations of 30 µm in BJAB cells, 20 µm in Nalm‐6 cells, 10 µm in resistant Nalm‐6 cells, and 5 µm in resistant BJAB cells. Unspecific cell death was excluded by LDH‐release assay. Abstract : A series of terpyridine and terpyridine‐analogous ligands bearing sugar moieties attached by different glycosidic bonds and their Ir III complexes was synthesized and characterized. Studies on cell viability, selectivity, drug resistance in vitro, and the apoptosis mechanism were performed. The results revealed enhanced activity of a complex bearing acetylated thioglucose.